Green synthesis of mixed metallic nanoparticles using room temperature self-assembly - Abdelghany, A. M.; Oraby, A.H.; Hindi, Awatif A; El-Nagar, Doaa M; Alhakami, Fathia S (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Bimetallic nanoparticles of silver (Ag) and gold (Au) were synthesized at room temperature using Curcumin. Reduction process of silver and gold ions with different molar ratios leads to production of different nanostructures including alloys and core-shells. Produced nanoparticles were characterized simultaneously with FTIR, UV/vis. spectroscopy, transmission electron microscopy (TEM), and Energy-dispersive X-ray (EDAX). UV/vis. optical absorption spectra of as synthesized nanoparticles reveals presence of surface palsmon resonance (SPR) of both silver at (425 nm) and gold at (540 nm) with small shift and broadness of gold band after mixing with resucing and capping agent in natural extract which suggest presence of bimetallic nano structure (Au/Ag). FTIR and EDAX data approve the presence of bimetallic nano structure combined with curcumin extract. TEM micrographs shows that silver and gold can be synthesized separately in the form of nano particles using curcumin extract. Synthesis of gold nano particles in presence of silver effectively enhance and control formation of bi-metallic structure.